PENGARUH MOTIVASI TERHADAP KINERJA GURU MTs. NEGERI DI KULON PROGO - Burhanudin Burhanudin; Sugihardi Sugihardi; Yayuk Apriyani (JURNAL LENTERA BISNIS, 2022)
This study aims to examine the effect of the need for achievement on teacher performance, examine the effect of the need for power on teacher performance, and examine the effect of the need for affiliation on teacher performance. Respondents in this study were 60 teachers at Madrasah Tsanawiyah in Kulon Progo Regency. A questionnaire was utilized to collect data, and multiple linear regression was employed to analyze it. The results showed that the need for achievement affects teacher performance, the need for power affects teacher performance, and the need for affiliation affects teacher performance.Keywords: the need for achievement, need for power, need for affiliation, teacher performance